Central Granular Cell Odontogenic Tumor: Report of a Case with CBCT Features. - Najmeh Anbiaee; Shadi Saghafi; Maryam Mohammadzadeh Rezaei (Tehran University of Medical Sciences, 2014)
Central granular cell odontogenic tumor) CGCOT) of the jaw is an exceedingly rare benign odontogenic neoplasm with 35 reported cases in the literature. Among these, very few studies have focused on the cone-beam CT features of CGCOT. Here, we report a case of an asymptomatic CGCOT in a 16-year-old girl and focus on the cone-beam CT features. Only 36 cases of this lesion, including this one, have been reported so far. The case presented is of special importance due to the young age of the patient, the posterior location of the lesion and the multilocular pattern in the cone beam CT images.